2022
DOI: 10.1038/s41598-022-07093-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between severity of COVID-19 infection during pregnancy and neonatal outcomes

Abstract: Pregnant women with COVID-19 require special attention and care, since the infection does not only affect the mother, but also her neonate and adversely affects pregnancy outcomes. The main goal of this retrospective cohort study is to investigate association between the maternal COVID-19 severity and risk of developing adverse neonatal outcomes. Patients were stratified into asymptomatic/mild and moderate to severe COVID-19. The following neonatal outcomes were assessed: gestational age at the time of deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 35 publications
6
28
0
2
Order By: Relevance
“…Increased risk of preterm delivery, lower birth weight, neonatal infection, and NICU admission were also reported in pregnant women with moderate to severe COVID-19 in U.A.E [26]. The neonates mainly presented with feeding difficulties (1.8%), respiratory distress (3.2%), and hyperbilirubinemia (4.04%) The fever and gastrointestinal symptoms were rare, similar to data from National Neonatology Forum, India, [24] not as common as reported in earlier studies [27].…”
Section: Discussionmentioning
confidence: 89%
“…Increased risk of preterm delivery, lower birth weight, neonatal infection, and NICU admission were also reported in pregnant women with moderate to severe COVID-19 in U.A.E [26]. The neonates mainly presented with feeding difficulties (1.8%), respiratory distress (3.2%), and hyperbilirubinemia (4.04%) The fever and gastrointestinal symptoms were rare, similar to data from National Neonatology Forum, India, [24] not as common as reported in earlier studies [27].…”
Section: Discussionmentioning
confidence: 89%
“…However, research on infectious and immune outcomes within this age group has been limited, with the notable exception of research on fetal, perinatal, and neonatal transmission risks (e.g. 12 14 ). Beyond the neonatal period, infants may be at heighted risk of SARS-CoV-2 transmission from infected caregivers due to the frequency and intensity of close contact care and feeding ( 15 , 16 ), and may have higher risks of severe infection relative to older children due to less developed immune responses ( 6 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is unique in that the predominant ethnicity of the mothers observed was Hispanic. Previous studies have noted the increased incidence of preterm births in infected mothers [ 26 , 27 , 28 , 29 ]. Our study shows no such risk, and we suggest that this may be explained by the fact that the majority of the infected mothers in our study did not suffer from severe symptoms or experience any major COVID-19 complications.…”
Section: Discussionmentioning
confidence: 99%